Food around the world a cultural perspective - McWilliams, Margaret; Heller, Holly (Prentice Hall, 2003)
Provides readers with a sound fundamental knowledge of the worldʼ s nations and the uniqueness of todayʼ s rich cultural patterns. Food is featured prominently because of its universal appeal and the meaningful ways that geography, climate, economics, and religion have combined with history and culture to define the ingredients and food patterns unique to countries and regions around the world. Offers readers recipes, maps, and photographs from such regions of the world as the British Isles, Scandinavia, Italy, Greece, Turkey, India, Southeast Asia, China, South America, and the Caribbean. For clinical dieticians and administrative dieticians in hospitals. Each chapter includes geographic overview, history and culture, food patterns, key terms, recipes, summary, study questions and bibliography.